2016
DOI: 10.2147/ijn.s112415
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of composite magnetic nanoparticles&nbsp;Fe<sub>3</sub>O<sub>4</sub>&nbsp;with alendronate for osteoporosis treatment

Abstract: Osteoporosis is a result of imbalance between bone formation by osteoblasts and resorption by osteoclasts (OCs). In the present study, we investigated the potential of limiting the aggravation of osteoporosis by reducing the activity of OCs through thermolysis. The proposed method is to synthesize bisphosphonate (Bis)-conjugated iron (II, III) oxide (Fe 3 O 4 ) nanoparticles and incorporate them into OCs. The cells should be subsequently exposed to radiofrequency (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(27 citation statements)
references
References 37 publications
3
24
0
Order By: Relevance
“…For our knowledge it is a first report showing that IOs can induce apoptosis specifically in osteoclasts while enhanced osteogenic properties of osteoblasts. Similar research has only been performed by Lee et al [51] who fabricated magnetic nanoparticles however with Fe 3 O 4 combined with alendronate for the treatment of osteoporosis. They have found that, fabricated nanoparticles decreased osteoclasts cell survival rate and be applied as a stable MRI contrast agent.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…For our knowledge it is a first report showing that IOs can induce apoptosis specifically in osteoclasts while enhanced osteogenic properties of osteoblasts. Similar research has only been performed by Lee et al [51] who fabricated magnetic nanoparticles however with Fe 3 O 4 combined with alendronate for the treatment of osteoporosis. They have found that, fabricated nanoparticles decreased osteoclasts cell survival rate and be applied as a stable MRI contrast agent.…”
Section: Discussionsupporting
confidence: 61%
“…For our knowledge this is a first report showing that Fe 2 O 3 nanoparticles are able to reduce osteoclasts activity. Research performed by Lee et al [51] revealed that similar to Fe 2 O 3 , Fe 3 O 4 nanoparticles doped with aldosterone, are able to control osteoporosis progression by destroying osteoclasts through thermolysis. Contrary to our results, it was also shown that iron can stimulate osteoclasts differentiation via NF-κB signalling pathway [52] and through increase of RANKL/reactive oxygen species levels [53].…”
Section: Discussionmentioning
confidence: 99%
“…Further preservation of supporting teeth and neighbouring alveoli by OD can be provided by inserting of small magnetic cylinders in its base under the remaining teeth. The constant magnetic field is beneficial in reducing the dental plaque index values 7 and food retention around the supporting teeth due to the poor oral hygiene at elders, what confirmed the 12-month study 4 .…”
Section: Check-upssupporting
confidence: 66%
“…Periodontal tissue that surrounds preserved remaining teeth, intact pulp and alveolar bone below OD may be additional positive biologically stimulated by installation of small magnets and their permanent irradiation 4,16 . The teeth with greater alveolar support and coronal mass should enter the list.…”
Section: Periodontologymentioning
confidence: 99%
See 1 more Smart Citation